Analisis persepsi siswa SMK Teladan Batam terhadap pembelajaran matematika di masa pandemi covid 19 ditinjau dari gaya belajar - Dian, Romika; Agustyaningrum, Nina; Hanggara, Yudhi (Karoteh Utama, 2021)
This research aims to explore students' perceptions at SMK Teladan Batam regarding mathematics education during the Covid-19 pandemic, focusing on the differences in individual learning styles. This study employs a qualitative descriptive approach, with the research subjects consisting of 35 students from class XI TEI. Data analysis is conducted using the Miles Huberman method. The research instruments include a learning style questionnaire comprising 24 statements and a perception questionnaire comprising 20 statements. These instruments have been tested for validity and reliability (r = 0.733), and their results are reinforced through interviews. The obtained data are analyzed descriptively, with students' perceptions divided into three indicators: acceptance, understanding, and assessment, while learning styles are categorized into three parts: visual, auditory, and kinesthetic. The research findings indicate that out of the 35 students, 19 have a visual learning style with a highly positive category, with a percentage of acceptance at 71.93%, understanding at 78.29%, and assessment at 75.49%. 13 students have an auditory learning style, with a percentage of acceptance at 72.44%, understanding at 75.64%, and assessment at 72.36%. Meanwhile, three students have a kinesthetic learning style, with a percentage of acceptance in learning at 72.22%, understanding at 75%, and assessment at 78.13%, all of which fall under the high category.